Methods of text figuration: types and functions of metaphors in the Zhyrau’s language (Eurasian Journal of Philology Science and Education, 2021)
In modern linguistics, the boundaries of understanding metaphor are expanded. Metaphor is recognized as a tool for knowing and modeling the environment, and the world around us. Indeed, the figurative and artistic expression of ideas was very important for the Kazakhs. This can be seen from the very beginning of reading the heritage of Zhyrau literature. The metaphor has long been a tool in the life of the Kazakh people for understanding the world. The article defines the main functions of the metaphor of the early centuries of the Kazakh literary language using statistics, through understanding the meaning and changing the meanings of words, through the definitions of active words and phrases of the zhyraus' language. According to this, the article defines some key metaphor-forming words of the Kazakh literary language of the early centuries, as well as important signs of the zhyrau period, types of metaphors, elucidated methods of metaphor-forming of those times, some structural, lexico-grammatical differences are indicated. Changes in the structures of metaphors in Zhyrau’s languages ​are determined, the influence of religious words in metaphor formations in some religious-educated zhyrau is indicated, and the functions of metaphors of those times are determined. Examples are given in the context, since the values ​ ​ of many metaphors are related to the context. The article reveals linguistic features, types, composition of metaphors typical for zhyrau, based on formed opinions, views, that is, it refers to scientific works known among linguists.Keywords: conceptual phenomenon, art metaphor, individual metaphor, metaphor riddle, comparison metaphor.